Inter-regional Mobility in the Accession Countries: A Comparison to EU-15 Member States - Peter Huber (Austrian Institute of Economic Research (WIFO), 2005)
This paper uses a data set covering 9 EU15 member states and 7 candidate countries and new member states to compare inter-regional migration patterns in the 1990s. We find that migration is lower in candidate countries and new member states than in EU15 member states. Also in contrast to the EU15 member states migration has fallen in candidate countries and new member states. This casts doubt on the viability of migration as an adjustment mechanism. Estimating place to place models of migration we find that migration is less reactive to regional disparities in candidate countries and new member states than in EU15 member states. If reaction to labor market disparities were similar to EU15 states net migration should increase by a factor of 2 to over 10.
Keywords: P25; J61; 330; Regional Labor Market Adjustment; Transition; EU Accession; Internationale Migration; Vergleich; EU-Mitgliedschaft; EU-Staaten; Mobilität; Migrationsforschung